Simplify the Expression and Find its Value when $a=5$ and $b=-3$.
$2(a^2+ab)+3-ab$

AcademicMathematicsNCERTClass 7

Given: Expression: $2(a^2+ab)+3-ab$

To do: To simplify the Expression and Find its Value when $a=5$ and $b=-3$.

Solution:

From the question it is given that $a=5$ and $b=-3$

We have,

$=2a^2+2ab+3-ab$

$=2a^2+ab+3$

Then, Substitute the value of $a$ and $b$ in the Equation

$=(2\times 5^2)+(5\times (-3))+3$

$=(2\times 25)+(-15)+3$

$=50 - 15+3$

$=53-15$

$=38$
raja
Updated on 10-Oct-2022 13:38:20

Advertisements